The rise of Evo Morales and the MAS - Harten, Sven (Zed Books ; Distributed in the USA exclusively by Palgrave Macmillan, 2011)
In this insightful and revealing book, Sven Harten explains the success of the MAS and its wider consequences, showing how Morales has become the symbol for a new political consciousness that has entailed de-stigmatizing Indigenous identities. It reveals the challenge of squaring the rupture with a discredited past with the continuity of democracy and the aim of representing an entire society.